2008
DOI: 10.2202/1542-0485.1235
|View full text |Cite
|
Sign up to set email alerts
|

Scitovsky Reversals and Efficiency Criteria in Policy Analysis

Abstract: Lawyers and philosophers have used the Scitovsky paradox to discredit cost-benefit analyses. His paradox is used as a criticism of the potential compensation criterion. But the occurrence of reversals is severely limited. The Compensation Principle, even with its potential nature, requires that compensation actually could be paid. Based on many empirical cost-benefit studies, the actual cost of compensation, which includes transaction costs, can be large. The attempt at actual compensation could turn a highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Markovits (1993) goes even further and claims that the possibility of such reversals renders all welfare economics' arguments wrong. Elsewhere, Schmitz and Zerbe (2008) have shown that the technical arguments of Coleman and Markovits are incorrect, relying on second best situations. 9 The Posner and Alder comment remains germane to some extent.…”
Section: Scitovsky Reversalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Markovits (1993) goes even further and claims that the possibility of such reversals renders all welfare economics' arguments wrong. Elsewhere, Schmitz and Zerbe (2008) have shown that the technical arguments of Coleman and Markovits are incorrect, relying on second best situations. 9 The Posner and Alder comment remains germane to some extent.…”
Section: Scitovsky Reversalsmentioning
confidence: 99%
“…The compensating variation is a necessary but not a sufficient condition to pass the PCT, while the EV is sufficient but not necessary(Broadway & Bruce, 1984). (See alsoSchmitz & Zerbe, 2008).…”
mentioning
confidence: 99%
“…2 The purpose of this paper is to show that, although important concerns have been raised about the PCT, 3 the reversal paradox is not one of them. Recently, Schmitz and Zerbe (2008) have shown several cases where reversals are unlikely in most practical applications of benefit-cost analysis. For example, 1 Technically, there are two compensation criteria (Coate, 2000).…”
Section: Introductionmentioning
confidence: 99%